Effect of histamine blockers on histamine induced decrease in lecithin levels in BAL(Broncho alveolar lavage) fluid in rats - Rao, G. Janardhana (1999)
Lecithin,a major surface active substance of surfactant system of lung was estimated in bronchoalveolar lavage (BAL) fluid in four groups of healthy adult male albino rats. Rats from group I were not administered any drug and acted as controL Group II were administered histamine diphosphate. Group III were given H1 blocker (Pyrilamine maleate) followed by histamine diphosphate. Group IV received H2 blocker (Ranitidine hydrochloride) followed by histamine diphosphate. Lecithin content of BAL fluid in control group was compared with that in the other three groups. A significant decrease in lecithin content was observed in the rats that received either histamine diphosphate or H1 blocker followed by histamine diphosphate. However, compared to control rats no significant difference in lecithin content was seen in the rats that received H2 blocker followed by histamine diphosphate. The results clearly indicate that the decrease in surface active lecithin content in BAL fluid following administration of histamine diphosphate was unaffected by prior administration of H 1 blocker. but was blocked by prior administration of H1 blocker. It was concluded that histamine induced decrease in lecithin content of BAL fluid is mediated through H~ receptors. Since the predominant source of intraalveolar lecithin is secretion of Type II cells of alveolar epithelium, it is possible that Type II cells have H2 receptors, stimulation of which resulted in decreased intraalveolar lecithin.